Safety at sea during the Industrial Revolution - Morgan Kelly; Cormac Ó Gráda; Peter M. Solar (University College Dublin, UCD Centre for Economic Research, 2019)
Shipping was central to the rise of the Atlantic economies, but an extremely hazardous activity: in the 1780s, roughly five per cent of British ships sailing in summer for the United States never returned. Against the widespread belief that shipping technology was stagnant before iron steamships, in this paper we demonstrate that between the 1780s and 1820s, a safety revolution occurred that saw shipping losses and insurance rates on oceanic routes almost halved thanks to steady improvements in shipbuilding and navigation. Iron reinforcing led to stronger vessels while navigation improved, not through chronometers which remained too expensive and unreliable for general use, but through radically improved charts, accessible manuals of basic navigational techniques, and improved shore-based navigational aids.
Keywords: N00; N73; G22; 330; shipping; insurance; Industrial Revolution